Predictive model for patients with poor-grade subarachnoid haemorrhage in 30-day observation: a 9-year cohort study. Issue 6 (12th June 2015) - Szklener, Sebastian; Melges, Anna; Korchut, Agnieszka; Zaluska, Wojciech; Trojanowski, Tomasz; Rejdak, Robert; Rejdak, Konrad
Abstract : Objective: The purpose of this study was to identify prognostic factors and build the predictive model based on poor-grade subarachnoid haemorrhage (SAH) population received only supportive symptomatic treatment. Design: Prospective observational cohort study. Setting: Intensive care unit at the Clinical Department of Neurology. Participants: A total of 101 patients with spontaneous SAH disqualified from neurosurgical operative treatment due to poor clinical condition. Data were collected over a 9-year period. Outcome measures: Unfavourable outcome was defined as a modified Rankin Score ≥5 at 30 days of observation. Results: Multivariable logistic regression analysis indicated the World Federation of Neurosurgical Societies Scale score, increasing age, Fisher grade and admission leucocytosis as independent predictive factors. The proposed scale subdivides the study population into four prognostic groups with significantly different outcomes: grade I: probability of favourable outcome 89.9%; grade II: 47.5%; grade III: 4.2%; grade IV: 0%. The receiver operating characteristic (ROC) curve for the prediction of outcome performed by the new scale had an area under the curve (AUC)=0.910 (excellent accuracy). Conclusions: Unfavourable outcome in non-operated patients with poor-grade SAH is strongly predicted by traditional unmodifiable factors such as age, amount of bleeding in CT, level of consciousness as well as leucocytosis. A new predictive scale based on the above parameters seems to reliably predict the outcome and may contribute to more effective planning of therapeutic management in patients with poor-grade SAH.